2004
DOI: 10.1038/modpathol.3800137
|View full text |Cite
|
Sign up to set email alerts
|

Protein overexpression and gene amplification of HER-2 and EGFR in colorectal cancers: an immunohistochemical and fluorescent in situ hybridization study

Abstract: Overexpression of HER-2 and the epidermal growth factor receptor (EGFR) has been observed in many cancers, sometimes accompanied by gene amplification. To assess whether novel chemotherapies targeting these overexpressed proteins may be effective for the treatment of colorectal cancers, we examined the exact frequency of HER-2 and EGFR overexpression, the relationship between gene amplification and protein expression, and the heterogeneity of gene amplification within and between primary and metastatic tumors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
135
2
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(154 citation statements)
references
References 31 publications
13
135
2
4
Order By: Relevance
“…The frequency of gene amplification, on the other hand, is only 12% in primary colorectal carcinomas and 8% in metastases. The presence of a small but defined proportion of colorectal cancers that show EGFR gene amplification is in agreement with a recent report that used fluorescent in situ hybridization and IHC, 32 but differ from earlier studies that used Southern blot-or polymerase chain reaction (PCR)-based methods. In studies that used Southern blotting 33 or PCR, 34 no gene amplification was demonstrated in colorectal carcinoma cell lines or tissues microdissected from paraffin blocks, despite the presence of protein expression.…”
Section: Resultssupporting
confidence: 88%
“…The frequency of gene amplification, on the other hand, is only 12% in primary colorectal carcinomas and 8% in metastases. The presence of a small but defined proportion of colorectal cancers that show EGFR gene amplification is in agreement with a recent report that used fluorescent in situ hybridization and IHC, 32 but differ from earlier studies that used Southern blot-or polymerase chain reaction (PCR)-based methods. In studies that used Southern blotting 33 or PCR, 34 no gene amplification was demonstrated in colorectal carcinoma cell lines or tissues microdissected from paraffin blocks, despite the presence of protein expression.…”
Section: Resultssupporting
confidence: 88%
“…For example, HER-2 overexpression was shown in 5.7-88.8% of non-small-cell lung cancers 10,11 and 3.0-54% of colon cancers. 12,13 To a smaller extent, this variability is also observed in amplification analysis. Different methods for analysis (Southern blot or fluorescent in situ hybridization (FISH)) and definitions of amplification have resulted in variable frequencies of amplification reported in the literature such as 0-66% in ovarian cancer 14,15 or 6-56.2% in breast cancer.…”
mentioning
confidence: 77%
“…Some studies have suggested that the mechanisms of EGFR protein overexpression vary depending on tumor type. For example, gene amplification has been implicated as a major cause of EGFR protein expression in glioblastomas, 22 esophageal squamous cell carcinoma, 23 and colon carcinoma, 24 whereas the relationship between EGFR protein expression and gene amplification or mutation is not clearly understood in lung carcinoma. Some studies observed that somatic mutations of EGFR tyrosinekinase domain of non-small-cell lung carcinomas were associated with immunoexpression, 6 while other studies have shown that overexpression of EGFR was better associated with EGFR amplification or polysomy.…”
Section: Discussionmentioning
confidence: 99%